2017
DOI: 10.1016/j.joi.2017.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Improving fitness: Mapping research priorities against societal needs on obesity

Abstract: Science policy is increasingly shifting towards an emphasis in societal problems or grand challenges. As a result, new evaluative tools are needed to help assess not only the knowledge production side of research programmes or organisations, but also the articulation of research agendas with societal needs. In this paper, we present an exploratory investigation of science supply and societal needs on the grand challenge of obesity -an emerging health problem with enormous social costs. We illustrate a potentia… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 30 publications
1
34
0
Order By: Relevance
“…Science mapping has been extensively used in the context of research evaluation for identifying research priorities (Cassi et al 2017), to aid governance of specific areas (Rotolo et al 2014) or to profile institutions' research portfolio (Rafols, Porter and Leydesdorff 2010). The expansion of science mapping applications is largely derived to the free availability of academic software and tools that are constantly maintained and updated (Cobo et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Science mapping has been extensively used in the context of research evaluation for identifying research priorities (Cassi et al 2017), to aid governance of specific areas (Rotolo et al 2014) or to profile institutions' research portfolio (Rafols, Porter and Leydesdorff 2010). The expansion of science mapping applications is largely derived to the free availability of academic software and tools that are constantly maintained and updated (Cobo et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…There is a clear agreement between the results of both mappings that it is the themes of food environment and childhood obesity that connect the most thematic blocks and field-specific approaches (though the multicluster view picture school-related issues as constantly on the surface, for key concepts there seems to be a shift of emphasis towards family-related factors, such as the role of parents). The topics emerged in our mapping are also comparable to those identified in Cassi et al (2017) as "social issues"/"social environment", which is fairly acceptable for studies with a policy focus. On the other hand, there seems to be an increasing contribution from individual health-related fields, with closer proximity to the clinical sciences, viz.…”
Section: Discussionmentioning
confidence: 51%
“…The topical organization of (NHLBI-) funded projects and the productivity and impact of individual topics was the key issue for Nicastro et al (2016). However, probably the most extensive approach, being also the most relevant to our present work, has been provided in a series of recent papers best exemplified by Cassi et al (2017). The main objective of this work was a large-scale bibliometric mapping of the intellectual structure of obesity research in general, and contrasting it with the societal demands, also formalized into a topic map (based on European parliament questions) so that the concordances between the two maps could be analyzed.…”
Section: Related Work On Obesitymentioning
confidence: 99%
“…For public health concerns like obesity, the alignment/misalignment between the research community and societal interests has been explored. Cassi et al (2017) explored societal demands through the questions received by the European Parliament between 2009-2014 and found that a few topics identified by the public, such as sugar and food economy, are ignored by the scientific community and also that obesity research mainly focuses on biomedical science while largely neglecting socio-economic factors (Cassi et al, 2017). Similarly, misalignments were found between public health issues measured through disease burden rate and the amount of research done on the same issues.…”
Section: Research Alignment With Public Needsmentioning
confidence: 99%